On the third order boundary value problems with asymmetric nonlinearity - Smirnov, Sergey (Nonlinear Analysis: Modelling and Control, 2011)
The author considers two point third order boundary value problem with asymmetric nonlinearity. The structure and oscillatory properties of solutions of the third order nonlinear autonomous ordinary differential equation are discussed. Results on the estimation of the number of solutions to boundary value problem are provided. An illustrative example is given.
Keywords: boundary value problem with asymmetric nonlinearity; oscillatory properties of solutions; estimation of the number of solutions